A new Spanish and English dictionary: collected from the best Spanish authors, both ancient and modern. Containing several thousand words more than any other dictionary; with their etymology; their proper, figurative, burlesque and cant significations; the common terms of arts and sciences; the proper names of men; the surnames of families, and and account of them; the titles of the nobility of Spain; together with its geography, and that of the West Indies; with the names of such provinces, towns and rivers in other parts which differ in Spanish from the English. Also above two thousand proverbs literally translated, with their equivalents, where any could be found; and many thousands of phrases and difficult expressions explain'd. All the words throughout the dictionary accented, for the ascertaining of the pronunciation. To which is added, a copious English and Spanish dictionary. Likewise a Spanish grammar, more complete and easy than any hitherto extant: wherein the Spanish dialogues that have been publish'd are put into proper English. / The whole by Captain John Stevens. (2026)
Summary goes here